CEJA as a Place of Memories (Research, Society and Development, 2021)
This study presents a research excerpt carried out in the Postgraduate Program, Master in Teaching, PPGEN/UNIC/IFMT, analysis of the pedagogical organization in quarters by knowledge area implemented in CEJAS Centers for Youth and Adult Education in Mato Grosso by through memories and narratives of students and teachers who experienced the proposal between 2008 and 2016, as a way to create files, organize the actions carried out, as these interventions are socially produced. However, the acceleration of time makes us forget or disregard the past, making it necessary to ground collective memories. The methodology of this research is classified as a qualitative documentary and narrative study considering that the official documents of this period are initial data to represent the existence of memories (curriculum, planning and evaluation), as well as the identification of the role of EJA Centers in policies educational institutions of the State. And the participants' narratives represent the records of this space of memories and representations of school culture. As a result, we show that social groups build their narratives based on the memory of the experience, whether through writing, in this study the documents or oral presentations present in the interviews that unfortunately have been disregarded when it comes to the elaboration and continuity of educational public policies.